Offences and Procedures in the Iranian and United State Capital Markets - Chakusari, Mahdi Ashourzadeh; Zadeh, Mohsen Shekarchi; Masoud, Gholamhossein (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract Economic development in today's societies has provided the bad for the development of economic offences and consequently. Today, one of the simplest and sometimes safest ways to make money can be an investment in the field of the stock exchange. Investing personal money through investment in the economic cycle has helped the economic cycle a lot and has prevented inflation and stagnation in this cycle and on the other hand. It has provided conditions for some offences. The stock exchange can be a good platform to commit classic offences such as the betrayal of trust, theft and fraud and also can ease offences such as different types of fraud, cybercrimes and so on. Therefore, the governments have always thought about controlling and protecting the capital and the investors to prevent the chaos in the stock exchange and consequently, the economy of the society. The actions of activists in the capital market, which are against the principles and regulations of the market can be classified into 3 groups: 1. Regulative offences 2. Disputes 3. Offences. The occurrence of any of these acts is inevitable and can pave the way for distort of regulation and the security of governor on the investment activities of the states. Therefore, this study has attempted to consider the abovementioned issues as much as possible in Iran and US countries. Then, the study tends to analyze and investigate the supervising officials and tends, at last, to present types of lawsuits and procedures for them in the field of the stock exchange.Keywords: Stock Exchange, Exchange Crimes, Exchange Offences, Exchange Offence Investigation AbstrakPerkembangan ekonomi di masyarakat saat ini telah memberikan dampak buruk bagi perkembangan pelanggaran ekonomi dan akibatnya. Saat ini, salah satu cara paling sederhana dan terkadang teraman untuk menghasilkan uang adalah dengan berinvestasi di bidang bursa saham. Menginvestasikan uang pribadi melalui investasi dalam siklus ekonomi telah banyak membantu siklus ekonomi dan telah mencegah inflasi dan stagnasi dalam siklus ini dan sebaliknya. Ini telah memberikan kondisi untuk beberapa pelanggaran. Bursa saham dapat menjadi platform yang baik untuk melakukan pelanggaran klasik seperti pengkhianatan kepercayaan, pencurian dan penipuan dan juga dapat meringankan pelanggaran seperti berbagai jenis penipuan, kejahatan dunia maya dan sebagainya. Oleh karena itu, pemerintah selalu memikirkan untuk mengontrol dan melindungi modal dan investor untuk mencegah terjadinya kekacauan di bursa efek dan akibatnya, perekonomian masyarakat. Tindakan para pegiat pasar modal yang bertentangan dengan prinsip dan ketentuan pasar dapat diklasifikasikan menjadi 3 kelompok: 1. Tindak pidana regulasi 2. Sengketa 3. Pelanggaran. Terjadinya salah satu tindakan ini tidak dapat dihindari dan dapat membuka jalan bagi distorsi regulasi dan keamanan gubernur atas kegiatan investasi negara. Oleh karena itu, studi ini berusaha untuk sedapat mungkin mempertimbangkan masalah-masalah tersebut di atas di negara-negara Iran dan AS. Kemudian, studi ini cenderung menganalisis dan menyelidiki aparat pengawas, dan pada akhirnya cenderung menyajikan jenis-jenis tuntutan dan tata cara di bidang bursa.Kata Kunci: bursa efek, kejahatan bursa, delik pertukaran, investigasi tindak pidana bursa АннотацияТекущее экономическое развитие в обществе негативно сказалось на развитии экономических нарушений и их последствий. Сегодня один из самых простых и иногда самых безопасных способов заработать деньги - это инвестировать в фондовую биржу. Вложение личных денег посредством инвестирования в экономические циклы помогло экономическим циклам и предотвратило инфляцию и стагнацию в них, и наоборот. Это создало условия для совершения нескольких преступлений. Фондовая биржа может быть хорошей платформой для совершения классических преступлений, таких как обман доверия, кража и мошенничество, а также может смягчать такие преступления, как различные виды мошенничества, киберпреступность и т. д. Поэтому правительство всегда думает о контроле и защите капитала и инвесторов, чтобы предотвратить хаос на фондовой бирже и, как следствие, защитить народную экономику. Действия участников рынка капиталов, противоречащие рыночным принципам и нормам, можно разделить на 3 группы: 1. Нормативные преступления 2. Споры 3. Нарушения. Совершение одного из этих действий неизбежно и может приводить к регулирующим и безопасным действиям губернатора для инвестиционной деятельности страны. Таким образом, данное исследование направлено на то, чтобы как можно больше рассмотреть эти проблемы в Иране и США. Затем в этом исследовании анализируется и исследуется надзорный аппарат, и, наконец, представлены типы требований и процедуры в области фондовой биржи.Ключевые слова: Фондовая биржа, биржевое преступление, обменное преступление, расследование биржевого преступления.